ANALISIS METODOLOGI TAFSIR MARAH LABID : TAFSIR MUNIR KARYA SYAIKH NAWAWI AL-BANTANI - Tarto, Tarto (IAINU Kebumen Prodi IAT, 2022)
Interpretation of the Qur'an for Muslims is a relentless task. Tafsir is an endeavor to understand God's message in the Qur'an, which is an indication of what He wills. Therefore, the urgency of interpretation is very clear, but humans can only arrive at a relative degree of understanding, and not arrive at an absolute position. In the history of the development of interpretation, we have been able to find various kinds of products of different interpretations. We can also know that many Muslim scholars are involved in this matter in order to explore the deepest meaning contained in the Qur'an, especially in Indonesia. Studies from various sources have shown that the enthusiasm for studying the Qur'an since the arrival of Islam in Indonesia was quite high with several concentrations of study. Most of the commentary works written by Indonesian scholars filled the need for interpretive literature for their time. The majority of these interpretations are written in Javanese in pegon Arabic letters or Latin script, but there are several works of interpretation by Indonesian scholars who speak Arabic and are phenomenal which are still taught in Islamic boarding schools in Indonesia, namely the works of Shaykh Nawawi al-Bantani , known as Marâh Labid Tafsir al-Nawâwî or also known as Tafsir al-Munir.